Long term use of eltrombopag in children with chronic immune thrombocytopenia: extended real life retrospective multicenter experience of the Italian Association of Pediatric Hematology and Oncology - Giordano, Paola; Lassandro, Giuseppe; Barone, Angelica; Cesaro, Simone; Fotzi, Ilaria; Giona, Fiorina; Gorio, Chiara; Maggio, Angela; Miano, Maurizio; Marzollo, Antonio; Nardi, Margherita; Pession, Andrea; et al. (Frontiers in Medicine, 2023)
Background The present multicenter retrospective study on eltrombopag administration in Italian children with chronic ITP aims to extend follow-up of our previous study. Materials and methods This retrospective multicenter study was conducted in 17 centers affiliated to the Italian Association of Pediatric Hematology and Oncology (AIEOP). Patients were classified into three subgroups: group 1 included patients who discontinued treatment due to a stable platelet count; group 2 included patients who discontinued treatment due to ineffectiveness; group 3 included patients who did not permanently discontinue treatment. Results 56 patients were eligible for analysis. The median duration of eltrombopag treatment was 40 months (7–71 months). Twenty patients (36%) discontinued permanently eltrombopag. The reasons of permanent discontinuation were adverse effects (n = 1), inefficacy (n = 10), stable platelet count (n = 9). All patients of group 1 maintained a durable response without additional treatments after eltrombopag discontinuation. We found that patients of group 2 were on treatment for less time (median treatment time: 13.5 months, min: 6.0 – max: 56.0) than patients of group 1 (median treatment time: 34 months, min: 16.0 – max: 62.0) (p < 0.05). Patients of group 2 mostly did not achieve a stable platelet count in the first 6 months of treatment and underwent concomitant therapies during follow-up respect of group 1 and group 3 (p < 0.01). Conclusion Our study found that the benefits of eltrombopag treatment, in terms of platelet count improvement and use of additional therapies, are identifiable from the first 6 months of treatment.